Ablation of C-fibers decreases quantal size of GABAergic synaptic transmission in the insular cortex. (4th December 2017) - Murayama, Shota; Yamamoto, Kiyofumi; Kaneko, Mari; Ogiso, Bunnai; Kobayashi, Masayuki
Highlights: Insular cortex processes nociceptive information mediated via Aδ- and C-fibers. We tested if C-fiber ablation by capsaicin alters cortical GABAergic synapses. Capsaicin-treated rats showed enhanced excitatory propagation in insular cortex. C-fiber ablation depressed GABAA -mediated IPSCs by decreasing quantal content. These results contribute to elucidate a mechanism for induction of chronic pain. Abstract: The primary sensory cortex exhibits neuroplastic changes responding to sensory disturbances, and GABAergic synaptic transmission plays a critical role in the regulation of plasticity. The insular cortex (IC) integrates orofacial nociceptive signals conveyed via myelinated Aδ- and unmyelinated C-fibers. However, it has been unknown whether a disturbance of nociceptive inputs, such as a deletion of the peripheral nerves, alters GABAergic local circuit in IC. The present study elucidated GABAergic synaptic transmission in the model rat whose C-fibers were ablated by capsaicin injection 1–2 days after birth. In vivo optical imaging revealed that capsaicin-treated rats showed a facilitative excitatory propagation in IC responding to dental pulp stimulation. Whole-cell patch-clamp recording from pyramidal neurons (Pyr) demonstrated that capsaicin-treated rats showed the smaller amplitude of miniature inhibitory postsynaptic currents (IPSCs) than sham-treated rats without changing the frequency. Furthermore, replacement of extracellular Ca 2+ to Sr 2+, which induces an asynchronous release of neurotransmitters in the quantal size, induced a smaller amplitude of asynchronous unitary IPSCs recorded from fast-spiking GABAergic interneuron to Pyr connections in capsaicin-treated rats than sham-treated rats. These results suggest that capsaicin treatment depresses IPSCs via a postsynaptic mechanism. To confirm this possibility, the variance-mean analysis of unitary IPSCs was employed and we found that quantal size of GABAergic synaptic transmission was smaller in capsaicin-treated rats than in sham-treated rats. These results suggest that ablation of C-fibers induces plastic changes in GABAergic synaptic transmission by decreasing postsynaptic GABAA receptor-mediated conductance, which is a possible mechanism of the facilitative excitation in IC of capsaicin-treated rats.